PENGARUH PASAR TENAGA KERJA, KOMPENSASI FINANSIAL, DISRUPSI AKUNTAN DAN LINGKUNGAN KERJA DALAM KARIR AKUNTAN: LABOR MARKET CONSIDERATIONS, FINANCIAL REWARDS, DISRUPTION OF ACCOUNTANT PROFESSION AND WORK ENVIRONMENT ON CAREER AS ACCOUNTANT - Emrinaldi Nur DP (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
The purpose of this study is to examine empirically the effect of labor market considerations, financial rewards, disruption of the accounting profession, and work environment on the career interest of accounting students to become public accountants. The subjects of this study were accounting students at Riau University class 2017 and 2018 who had taken audit 1 and audit 2. The sample in this study amounted to 83 respondents were distributed online via google form then the data was processed using smart PLS software. The results of hypothesis testing at a significance level of 0.05 indicate that labor market considerations and financial rewards have a significant effect on career interest in becoming a public accountant. Variables disrupstion of the accounting profession and the work environment do not have a significant effect.